2011
DOI: 10.1002/ajmg.a.34293
|View full text |Cite|
|
Sign up to set email alerts
|

Having a son or daughter with Down syndrome: Perspectives from mothers and fathers

Abstract: This study asks parents who have children with Down syndrome how they feel about their lives so that such information could be shared with expectant couples during prenatal counseling sessions. A valid and reliable survey instrument was mailed to 4,924 households on the mailing lists of six non-profit Down syndrome organizations. Of the 2,044 respondents, 99% reported that they love their son or daughter; 97% were proud of them; 79% felt their outlook on life was more positive because of them; 5% felt embarras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
129
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 60 publications
14
129
0
6
Order By: Relevance
“…Relatedly, the positive impact that children with DS have on their families' lives was clearly articulated by participants in this study, as in previous work 19,27,[30][31][32] . Together with data from several studies showing that individuals with DS are happy with their lives and have high self-esteem 33,34 , this undermines the assumption of individual suffering that is foundational to the medical model of disability from which the pursuit of a cure for DS has evolved 20 .…”
Section: Discussionsupporting
confidence: 69%
“…Relatedly, the positive impact that children with DS have on their families' lives was clearly articulated by participants in this study, as in previous work 19,27,[30][31][32] . Together with data from several studies showing that individuals with DS are happy with their lives and have high self-esteem 33,34 , this undermines the assumption of individual suffering that is foundational to the medical model of disability from which the pursuit of a cure for DS has evolved 20 .…”
Section: Discussionsupporting
confidence: 69%
“…However, previous research has demonstrated that despite the length of time since diagnosis for some parents, their recollections of the process of diagnosis were very strong; these have been described as 'flash bulb memories' 40 and noted in other studies. 41,42 All of the mothers who were interviewed were recruited through a pre-existing database. This database was created when mothers who were interested in KS research contacted a senior researcher.…”
Section: Discussionmentioning
confidence: 99%
“…Tener un hijo o una hija con síndrome de Down ha sido identificado como una contecimiento estresante en la literatura. Así, Skotko et al (2011a) investigaron las actitudes de una muestra de 2.044 padres de niños con síndrome de Down. El 99% de los padres dijeron querer a su hijo, el 97% se sentían orgullosos de ellos, el 79 % decían haber mejorado su concepción de la vida a causa de su hijo, el 5% se avergonzaban de su hijo y el 4% mostraba pesar por tenerlo.…”
Section: Antecedentesunclassified